Transformation of education in landscape architecture through digitalisation of Heritage - Nizarudin, Norhanis Diyana; Zakariya, Khalilah; Ibrahim, Putri Haryati; Md Jani, Haza Hanurhaza (Institute of Landscape Architects Malaysia, 2023)
Landscape Architecture education is a dynamic process that requires agility and adaptability. A transformative approach is crucial for LA education to be future-proof, by keeping abreast with digitalisation and technology, while still integrating the values of art and science, as well as nature and culture. Post-pandemic has pushed the integration of hybrid learning, where the optimisation of computer-aided software, virtual and augmented reality, and collaborative work methods contribute to making education as a green and sustainable practice, which aligns with LAA2050, SDG, 4IR Policy, and the recent Malaysia Madani that emphasises on ‘smart and sharp’ graduates. Digitalisation in LA education not only benefitted teaching and learning, but became a critical tool for documenting, disseminating, and creating awareness towards the conservation of natural and cultural heritage.